PENGEMBANGAN MOBILE LEARNING UNTUK PEMAHAMAN KONSEP PADA MATA PELAJARAN SEJARAH INDONESIA MATERI KEHIDUPAN PRAAKSARA DI INDONESIA UNTUK KELAS X SMK NEGERI 10 SURABAYA - Anggraeni, Sherly; Kristanto, Andi (Jurnal Mahasiswa Teknologi Pendidikan, 2025)
ABSTRACT This research was driven by students’ difficulties in understanding the concept of Indonesian History, particularly the topic of prehistoric life. Existing media were mainly textbooks and verbal explanations, which were insufficient for the abstract nature of the material. This study aims to develop and test the feasibility and effectiveness of mobile learning media based on smartphone applications to improve conceptual understanding in history learning. The research employed the R&D (Research and Development) model by Sugiyono, limited to nine stages. Subjects included material experts, media experts, and tenth-grade RPL students at SMK Negeri 10 Surabaya. Expert validation results indicated a 100% feasibility rate categorized as “very feasible”, and effectiveness tests showed a significant value of sig. (2-tailed) = 0.00 < 0.05. The results suggest that the developed mobile learning media is both feasible and effective in enhancing students’ conceptual understanding of prehistoric life in Indonesia.